Evaluation of β-Sitosterol Loaded PLGA and PEG-PLA Nanoparticles for Effective Treatment of Breast Cancer: Preparation, Physicochemical Characterization, and Antitumor Activity - Moses Andima; Gabriella Costabile; Lorenz Isert; Albert J. Ndakala; Solomon Derese; Olivia M. Merkel (MDPI AG, 2018)
β-Sitosterol (β-Sit) is a dietary phytosterol with demonstrated anticancer activity against a panel of cancers, but its poor solubility in water limits its bioavailability and therapeutic efficacy. In this study, poly(lactide-co-glycolic acid) (PLGA) and block copolymers of poly(ethylene glycol)-block-poly(lactic acid) (PEG-PLA) were used to encapsulate β-Sit into nanoparticles with the aim of enhancing its in vitro anticancer activity. β-Sitosterol-loaded PLGA and PEG-PLA nanoparticles (β-Sit-PLGA and β-Sit-PEG-PLA) were prepared by using a simple emulsion-solvent evaporation technique. The nanoparticles were characterized for size, particle size distribution, surface charge, and encapsulation efficiency. Their cellular uptake and antiproliferative activity was evaluated against MCF-7 and MDA-MB-231 human breast cancer cells using flow cytometry and MTT assays, respectively. β-Sit-PLGA and β-Sit-PEG-PLA nanoparticles were spherical in shape with average particle sizes of 215.0 ± 29.7 and 240.6 ± 23.3 nm, a zeta potential of −13.8 ± 1.61 and −23.5 ± 0.27 mV, respectively, and with narrow size distribution. The encapsulation efficiency of β-Sit was 62.89 ± 4.66 and 51.83 ± 19.72 % in PLGA and PEG-PLA nanoparticles, respectively. In vitro release in phosphate-buffered saline (PBS) and PBS/with 0.2% Tween 20 showed an initial burst release, followed by a sustained release for 408 h. β-Sit-PLGA nanoparticles were generally stable in a protein-rich medium, whereas β-Sit-PEG-PLA nanoparticles showed a tendency to aggregate. Flow cytometry analysis (FACS) indicated that β-Sit-PLGA nanoparticles were efficiently taken up by the cells in contrast to β-Sit-PEG-PLA nanoparticles. β-Sit-PLGA nanoparticles were therefore selected to evaluate antiproliferative activity. Cell viability was inhibited by up to 80% in a concentration range of 6.64⁻53.08 μg/mL compared to the untreated cells. Taken together, encapsulation of β-Sitosterol in PLGA nanoparticles is a promising strategy to enhance its anticancer activity against breast cancer cells.